The Influence of Entrepreneurial Literacy and Personal Characteristics on Innovative Capabilities through Family Involvement as an Intervening Variable - Nur Kholifah; Nasikh; Agus Hermawan (Formosa Journal of Applied Sciences, 2023)
This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the given hypothesis. This research uses Google Forms to collect data on learning citizens at PKBM in Mojokerto Regency. Respondents in this study were 314 respondents from the three schools that were used as research objects. The results showed that Entrepreneurial Literacy could not explain Family Involvement. However, the Personal Characteristics variable can explain Family Involvement and Innovative Capability. Furthermore, Personal Characteristics will have more influence on Innovative Capability,ifstrengthened by Family Involvement as a mediator variable. Meanwhile, Entrepreneurial Literacy will not have a greater influence on Innovative Capability, even though it is strengthened by Family Involvement as a mediator variable.